2013
DOI: 10.1016/j.jdent.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Purpose, structure, and function of the United States National Dental Practice-Based Research Network

Abstract: Objective Following a successful2005–2012 phase with three regional practice-based research networks (PBRNs), a single, unified national network called “The National Dental PBRN” was created in 2012 in the United States to improve oral health by conducting practice-based research and serving dental professionals through education and collegiality. Methods Central administration is based in Alabama. Regional centres are based in Alabama, Florida, Minnesota, Oregon, New York and Texas, with a Coordinating Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 12 publications
0
106
1
1
Order By: Relevance
“…This research was conducted within the National Dental Practice-Based Research Network (23, 24); details are provided at http://nationaldentalpbrn.org/. The study methods have been previously reported (25) and pertinent points are presented below, conforming to STROBE guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…This research was conducted within the National Dental Practice-Based Research Network (23, 24); details are provided at http://nationaldentalpbrn.org/. The study methods have been previously reported (25) and pertinent points are presented below, conforming to STROBE guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Dental care has evolved slowly from the approach of restoring all carious lesions, regardless of size, to one of “early detection and management.” 16 Hamilton and colleagues 14 studied 223 QOC lesions in a randomized trial comparing air abrasion with monitoring over a two-year observation period. Only 16 percent (n = 100) of the lesions randomly assigned to the monitoring arm progressed into the dentin by the end of the two-year observation period on the basis of clinical examination, showing that conservation of tooth structure is possible.…”
Section: Discussionmentioning
confidence: 99%
“…The following regions participated in this study: Alabama/Mississippi (AL/MS), Florida/Georgia (FL/GA), Minnesota (MN) and Denmark (DK). The network subsequently evolved into its current form, 16 under the aegis of which we prepared the manuscript of this article. The respective institutional review board in each region approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…10111213 However, the National Dental Practice-Based Research Network has conducted studies of restorative treatment decisions that have included both questionnaire and clinical data. 14 Some network practitioners participated in both studies, which allowed the evaluation of concordance of treatment decisions across studies. Therefore, the objective for this study is to quantify the agreement between treatment recommended during hypothetical clinical scenarios and actual treatment provided in comparable clinical circumstances by the same dentists.…”
Section: Introductionmentioning
confidence: 99%